Risk Factors of the Elderly Falling in Public Hospitals: A Systematic Review Study - Masoumeh Otaghi1, Zahra Mohammad-Niakan2, Sanaz Aazami1, Ali Khorshidi3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Falls are the most common and problematic issue of old age. There is the possibility of falls among the elderly in the hospitals. The present study was conducted to determine the risk factors for falls in the elderly in hospitals through systematic review. Method: This is a systematic review based on the PRISMA protocol. The IranMedex, SID, Magiran, IranDoc, Medlib, Pubmed, Scopus, Web of Science, Science Direct, Medline and Google Scholar databases were searched for keywords in the time frame of 1994-2017. Results: The mean age was 64-81 years old and the number of elderly people varied from 88 to 28524 people. Of these studies, six studies were performed in the acute care unit, three studies in the elderly care unit, three studies in the surgical and clinical department, one study in the rehabilitation department, one study in the psychiatric department and other studies were performed in several parts of the hospital. The results of this study referred to individual and external factors as risk factors for the falls in the elderly in the hospital. The use of medications, physical problems, and psychological problems were the most common risk factors for falls in the elderly. Conclusion: In acute care, chronic care, psychiatric care, and elderly care units, there are many risk factors for the falls in the elderly due to their physical and mental status. Identifying and resolving these risk factors may provide safety for the elderly.